2019
DOI: 10.1002/hed.25683
|View full text |Cite
|
Sign up to set email alerts
|

Resected specimen size: A reliable predictor of severe Frey syndrome after parotidectomy

Abstract: Background: Frey syndrome is a common complication after parotidectomy. This study aimed to investigate the potential predictors for developing severe Frey syndrome after parotidectomy and to identify patients who may benefit from additional preventive maneuvers. Methods: A total of 485 patients received parotidectomy because of parotid tumors at the Otolaryngology Department of the National Cheng Kung University Hospital, from July 2009 to November 2015. Only 115 of 485 patients were included in this study an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…ROC analysis of the tumor sample diameter demonstrated that a resected sample with a larger area was correlated with a higher probability of Frey syndrome occurrence (AUC = 0.661). This finding was consistent with the results presented by Lin et al [ 12 ]. Therefore, it was concluded that the probability of Frey syndrome increased when the resected tumor diameter exceeded 4 cm[ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…ROC analysis of the tumor sample diameter demonstrated that a resected sample with a larger area was correlated with a higher probability of Frey syndrome occurrence (AUC = 0.661). This finding was consistent with the results presented by Lin et al [ 12 ]. Therefore, it was concluded that the probability of Frey syndrome increased when the resected tumor diameter exceeded 4 cm[ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 94%
“…This finding was consistent with the results presented by Lin et al [ 12 ]. Therefore, it was concluded that the probability of Frey syndrome increased when the resected tumor diameter exceeded 4 cm[ 12 , 13 ]. ADM can effectively prevent the occurrence of Frey syndrome after resection.…”
Section: Discussionsupporting
confidence: 94%
“…Postoperative sequelae, such as facial nerve dysfunction, facial depression, and gustatory sweating after parotid surgery may affect the quality of life of patients (11)(12)(13)(14). As only 55 patients were enrolled in this study and the follow-up period was not enough, it was not possible to generalize our results in the aspect of postoperative complications (15).…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, preauricular volume loss and Frey syndrome remain a concern in all parotidectomy patients and especially in those undergoing extensive resections. Lin et al 5 found that resections of tissue specimens greater than 40 mm in size could reliably ( P = 0.04; sensitivity, 71.7%; specificity, 42.0%) predict increased risk for development of severe Frey syndrome. Generally, smaller defects often require no reconstruction, whereas larger defects may be reconstructed by autogenous or allogenic grafts.…”
Section: Discussionmentioning
confidence: 99%